Publishing a research paper in reputable journals: doctoral students’ perspectives - Nur Hidayat; Slamet Setiawan; Syafiul Anam (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study aimed to enquire about the English foreign language (EFL) doctoral students’ perspective, especially in the non-English department, concerning the Indonesian government policy, which obliges an article published in a reputable international journal as a requirement to receive a doctoral degree. Their challenges in publishing their papers in Scopus or Web of Science (WOS)-indexed journals and their resolutions were also analyzed. A mixed-methods technique was used to obtain quantitative and qualitative information. The study consisted of 57 respondents, comprising 25 males and 32 females, who were EFL doctoral students of education departments from five universities. The purposive sampling method with several criteria was used to determine the study participants. Data were then collected through questionnaires and semi-structured interviews. Subsequently, the findings showed that the policy of publishing a paper in Scopus or WOS-indexed journals to obtain an EFL doctoral degree was burdensome to the majority of the students. Other findings showed that the students faced several challenges in publishing their papers in these journals, including language problems, cost of publication, journal selection, lack of experience, duration to publish, writing difficulties, revising, and stress. The actions to resolve these challenges were also provided in this study.